IC Efficiency and Firm Performance Among Industrial Companies in Jordan: An Extended Vaic Approach - Rawan Abdel Ghafour Jos; Norhayati Mat Husin; Hamza Ismail Hyarat (Migration Letters, 2023)
The purpose of this study is to investigate the impact of intellectual capital (IC), which include human, structural, relational, employed capital, and innovation, on the performance of industrial companies that are listed on the Amman Stock Exchange. In the present knowledge-driven era, the significance of IC has surpassed that of tangible assets and financial resources. IC has become a vital factor for economic progress, primarily due to the increasing value placed on intangible assets.Companies from industrial sector listed on the Amman Stock Exchange made up the study sample. Two hundred and thirty observations were sampled from panel data collected between 2014 and 2018 for this study. PLS was applied to analyse the collected data.The results of the regression analysis indicated a statistically significant link between human capital, capital employed, and company performance. However, no significant relationship was found between structural capital and firm performance.